Association between alcohol consumption and serum paraoxonase and arylesterase activities: a cross-sectional study within the Bavarian population. Issue 4 (15th January 2016) - Schwedhelm, Carolina; Nimptsch, Katharina; Bub, Achim; Pischon, Tobias; Linseisen, Jakob
Abstract: High alcohol consumption is an important risk factor for chronic disease and liver degeneration. Paraoxonase (PON1) and arylesterase (AE) are functions of the enzyme paraoxonase, which is synthesised by the liver. Paraoxonase circulates in plasma bound to HDL and hydrolyses lipid peroxides, protecting lipoproteins against oxidative modification. It has been shown that excessive alcohol consumption leads to a reduction of serum PON1 and AE activities; however, studies investigating the association with low and moderate alcohol consumption are scarce. We investigated the cross-sectional association between alcohol consumption and serum activities of PON1 and AE using data from the population-based Bavarian Food Consumption Survey II survey. PON1 and AE activities were quantified in serum samples of 566 male and female study participants (aged 18–80 years), and dietary intake including alcohol consumption was estimated from three 24-h dietary recalls. The association between alcohol consumption and PON1 and AE activities was analysed using linear regression, adjusted for age, sex and socio-economic status. There was no strong association between alcohol consumption and enzymatic activities of PON1 and AE in the Bavarian population. PON1 activity was seen to be lowest in non-drinkers (0 g/d) and highest in people who consumed 15·1–30 g of alcohol/d. AE activity increased across alcohol consumption categories, with a mean maximum difference of 14 U/ml ( P for linear trend 0·04). These associations were attenuated after adjustment for blood concentrations of HDL. The results of this study do not support the hypothesis that alcohol consumption is related to important alterations in PON1 and AE activities.